ChemInform Abstract: Bimetallic (Cu/Pd) Catalytic Cascade Reactions to 3, 3‐Disubstituted Oxindole Analogues. Issue 37 (16th September 2014) - Packer, Gemma; Lepre, Kurt; Kankanala, Jayakanth; Sridharan, Visuvanathar
Abstract Copper‐catalyzed click reactions followed by either a Pd‐catalyzed cyclization cross‐coupling or a cyclization‐carbonylation/amination process to title compounds (III) and (VIII) are reported.